Explaining party positions on decentralization - Toubeau, Simon; Wagner, Markus (Cambridge University Press, 2015)
Debates about decentralization raise cultural questions of identity and economic questions of redistribution and efﬁciency. Therefore the preferences of statewide parties regarding decentralization are related to their positions on the economic and cultural ideological dimensions. A statistical analysis using data from thirty-one countries conﬁrms this: parties on the economic right are more supportive of decentralization than parties on the economic left, while culturally liberal parties favour decentralization more than culturally conservative parties. However, country context – speciﬁcally the degree of regional self-rule, the extent of regional economic disparity and the ideology of regionalist parties – determines whether and how decentralization is linked to the two dimensions. These ﬁndings have implications for our understanding of the politics of decentralization by showing how ideology, rooted in a speciﬁc country context, shapes the ‘mindset’ of agents responsible for determining the territorial distribution of power.